The rule (x,y)→(−x,y) maps △ABC to △A′B′C′.Which statement correctly describes the relationship between △ABC and △A′B′C′ ?

The triangles are congruent because △A′B′C′ is a rotation of △ABC, and a rotation is a rigid motion.

The triangles are congruent because △A′B′C′
is a reflection of △ABC, and a reflection is a rigid motion.

The triangles are not congruent because △A′B′C′
is a translation of △ABC, and a translation is not a rigid motion.

The triangles are not congruent because △A′B′C′
is a reflection of △ABC, and a reflection is not a rigid motion.

Answers

Answer 1
Answer: Going from (x,y) to (-x,y) is telling us we have a reflection going on. For example, (1,2) will map to (-1,2). This is a reflection over the y axis (the vertical axis). A reflection will keep two points the same distance apart. So it preserves distances and side lengths. Therefore, if ABC is reflected over the y axis then A'B'C' is congruent to ABC. 

The final answer is choice B.
Answer 2
Answer:

The correct option is :

(B)The triangle are congruent because the triangle A'B'C' is a reflection of triangle ABC and a reflection is a rigid motion.

Step-by-step explanation:

Given information:

The rule (x,y) going to (-x,y) maps triangle ABC to Triangle A'B'C'

Now,

The reflection is going on if we are going from (x,y) to (-x,y)

For example the point (1,3) will map (-1,3) , this is a reflection over y axis.

A reflection will keep the two points the same distance apart so we can say it will preserve the side length and distance.

Hence, if triangle ABC is reflected over y axis then A'B'C' is congruent to ABC.

So, The correct option is :

(B)The triangle are congruent because the triangle A'B'C' is a reflection of triangle ABC and a reflection is a rigid motion.

For more information visit:

brainly.com/question/25063327?referrer=searchResults


Related Questions

A store is having a BOGO (buy one get on half off) sale. A customer buys 2 products that cost $40 and $30. Determine the total cost for the 2 items
A helicopter hovers at an altitude that is 1000 feet above a mountain of altitude 5210 feet. A second, taller peak is viewed from both the mountaintop and the helicopter. from the helicopter, the angle of depression is 43, and the mountaintop, the angle of depression is 18 degree. how far apart are the mountain peaks? what is the altitude of the taller peak?
PLS HELP ASAP!! THXFor questions 6-9 refer to the box plots (Assume their positions are on the same number line). Write your responses in complete sentences using content specific vocabulary.
The product of 12 and y increased by 11
How do I show the work for 5.4 divided by 39.42?

Multiply: (4x – 7)(2x – 9)

Answers

Hello there!


Let's use foil.

First: 4x * 2x = 8x^2

Outside: 4x * -9 = -36x

Inside: -7 * 2x = -14x

Last: -7 * -9 = 63


Now, let's combine these.

8x^2 - 36x - 14x + 63

Finally, we can simplify this

8x - 50x + 63



I hope I helped!

Let me know if you need anything else!

~ Zoe


X^{2} -25=0 Please help meeee

Answers

Answer:

x=5,x=-5

Step-by-step explanation:

x^2-25=0

Add 25 to both sides:

x^2-25+25=0+25

x^2=25

Square root both sides:

x=√(25),\:x=-√(25) (Since a negative number multiplied by itself gives positive, there are two answers.)

x=5,x=-5

Hey there!

ANSWER: x=5\nx=25

EXPLANATION:

x^2-25=0

The first step we have to do is to add 25 to both sides of the equation.

x^2-25+25=0+25\n\text {equals }x^2=25

In our last and final step, we will have to take the square root.

x= ±√(25)

We have two answers.

x=5(ANSWER)\nx=-5(ANSWER)

Hope this helps!

\text {-TestedHyperr}

125apples were shared between jerry and kay. kay received 20% less than jerry.

Answers

if that is the case, then Jerry got 60% and Kay received 40%, because together they make the 100%, or in equations:
kay + jerry = 100%
kay = jerry - 20%
substitute:
jerry - 20% + jerry = 100%
2*jerry = 120%
jerry = 60%
kay = jerry - 20% = 60% - 20%
kay = 40%
if you want to know the amount of apples each has:
kay = 40%(125) = 0.4(125)
jerry = 60%(125) = 0.6(125)

Hi,Can some one tell me how to solve this problem √-27 (step by step please)

Answers

The solution is short and simple: "A negative number has no real square root. There is no solution."
√-27=√-3*-3*-3=√ 3^{2} *(-3)=3√-3 is the ans 

X+y=0 and x-y=10 solve by substitution.. How do I figure out the problem!

Answers

x+y=0 \n x-y=10 \n\nx=-y\nx-y=10\n\n-y-y=10\n-2y=10\ny=-5\n\nx-5=0\nx=5\n\n\boxed{(x,y)=(5,-5)}
  x+y=0
- x-y=10
--------------
(0)+2y=-10 [x and -x cancel each other out. y minus -y is the same as y+y]
y=-5 
now substitute -5 in for y in either problem:

x+-5=0
x=5

How much would $600 invested at 8% interest compounded continuously be worth after 3 years? Round your answer to the nearest cent.

Answers

Answer:$762.73


Step-by-step explanation:


The answer would be 762.75

Hope this helps. Good luck!